Law Enforcement Of Crime Operation Power Installation Without Certificate Of Operations Eligible Under The Constitutional Court Decision Number 58 / Puu-Xii / 2014 (Overview Against Article 54 Paragraph 1 Of The Act Number 30/2009) - Alfian Faulia Numairi; Amin Purnawan (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2019)
Electricity policy in encouraging the ease of trying to become the hope of many parties. Act Number 30 of 2009 on Electricity requires that any electrical installation has the operational acceptance certificate (SLO). Based on the operational acceptance certificate as a prerequisite for enjoying the flow of electricity, as a discrimination against citizens and compounded by the threat of imprisonment related to the waiver provisions. The Constitutional Court is authorized to reconcile the justice seekers in the nation's leading citizens equal rights and away from discrimination. This study departs from problems such as the following: 1) How do criminal acts of law enforcement on power installations operate without a certificate of operation acceptance; 2) What factors affect the law enforcement of criminal acts operating electric power installations without a certificate of operation worthiness.This study uses empirical juridical approach to the type of descriptive analytical research. Data used by researchers there are two types of primary and secondary data. Primary data were obtained through interview and secondary data obtained by the engineering literature study.Based on the results, it can be explained that: 1) Law Enforcement Crime operate Installation Power Without Eligible Certificate of Operation, originated from Central Java Police open investigation investigators through interviews, with the results known to the criminal offense of electricity. Further enhanced the status of the investigation into the investigation process. At this stage of the prosecution, the public prosecutor indicted the suspect in the first alternative charges which violates Article 49 paragraph (2) or second violation of Article 54 paragraph (1) of Act Number 30 of 2009. 2) The factors that affect law enforcement Crime operate Installations power Without Eligible Certificate of Operation is the socialization factor that is still weak, criminals who do not know about the legal norms in Act Number 30 of 2009,Keywords: Criminal; Operational Acceptance Certificate; Electricity